The Filipino family in crisis ten case studies - Jamias, Eugenia C.
"These case studies seek to delve more deeply into the dynamics of the Filipino and his family. Through depth studies of ten patients, this casebook will explore the symptomatology, psychopathology, and the corresponding socio-cultural determinants. The project grew out of the questions raised during clinical case conferences and informal discussions among members of the team. Its objectives are: (1) To bring to light psychoanalytic theory as reflected in the clinical problems of Filipino patient. (2) To discuss in the clinical context Filipino values as they can be related to personality development. (3) To illustrate the diagnostic study of an individual using the team approach. (4) To provide a casebook for the use to students in psychiatry, psychology, social work and other related disciplines."--P. vii.